The evolving role of agriculture in Ethiopia's economic development - Dorosh, Paul A. (University of Pennsylvania Press, 2012)
Ethiopia is changing at an accelerating pace. Major investments in roads are bringing tens of millions of people effectively closer to major urban centers and services. Expansion of telecommunications, especially through cellular phones, likewise has connected much of the country and vastly improved the spread of information. The average electricity generation capacity during 1990–99 was 334 megawatts, and by 2010 that capacity had more than quadrupled, to 1,498 megawatts. During the same period, the capacity per capita almost tripled (from 6.0 watts to 17.4 watts). These advances are providing new opportunities for industrial production and modern services.